PENGARUH PROFITABILITAS, LIKUIDITAS DAN SIZE TERHADAP NILAI PERUSAHAAN DENGAN STRUKTUR MODAL SEBAGAI VARIABEL MODERATOR - Muhammad Nur Iman; Mr Rustam; Mr Mustaruddin (Equator Journal of Management and Entrepreneurship (EJME), 2023)
Maximizing company values is the goal of every company, especially profit-oriented ones. High company value indicates good company performance and also shows that management is managed effectively, so that the higher the value of a company, the better it will have an image. The purpose of this study is to test the effect of profitability, liquidity and size on the value of the company with the capital structure as a moderator variable. The population in this study is all companies included in the Kompas 100 index for the 2016-2020 period with sampling techniques using the purposive sampling method and obtained as many as 57 issuers who became research samples.     The data analysis technique used in this study is descriptive statistical analysis using a panel data regression model with three equation models processed using Eviews. The results of the analysis that has been carried out illustrate that profitability proxied using ROE has a positive effect on the value of the company, while liquidity and size do not affect the value of the company. The value of the variable coefficient of interaction of profitability and capital structure is significant and positively marked so that the capital structure can strengthen the effect of profitability on the value of the company while the capital structure does not affect the relationship of liquidity to the value of the company. Keywords: Company Value, Profitability, liquidity size and capital structure